Development and evaluation of ecoregion-based jack pine height-diameter models for Ontario - Zhang, Lianjun; Peng, Changhui; Huang, Shongming; Zhou, Xiaolu (The Forestry Chronicle, 2002)
The Chapman-Richards growth function is used to model jack pine (Pinus banksiana Lamb.) tree height-diameter relationships at provincial, regional, and ecoregional levels. The results suggest that the tree height-diameter relationships of jack pine are significantly different among the geographic regions of Ontario, depending on local climatic, soil, and ecological conditions. In light of this study, the provincial and regional height-diameter models are not appropriate for predicting tree heights at the ecoregional level. Further, applying a specific ecoregional model to other ecoregions will also result in significant biases for predicting local tree heights. The ecoregion-based height-diameter models developed in this study may provide more accurate information on tree growth and development to forest resource managers and planners. Key words: Chapman-Richards growth function, permanent sample plot, non-linear extra sum of square method, forest management

Modelling the influence of harvesting on Chinese boreal forest carbon dynamics - Jiang, Hong; Apps, Michael J; Peng, Changhui; Zhang, Yanli; Liu, Jinxun (Forest Ecology and Management, 2002)

Historic carbon budgets of Ontario’s forest ecosystems - Liu, Jinxun; Peng, Changhui; Apps, Mike; Dang, Qinglai; Banfield, Edwin; Kurz, Werner (Forest Ecology and Management, 2002)

A component object model strategy for reusing ecosystem models - Liu, Jinxun; Peng, Changhui; Dang, Qinglai; Apps, Mike; Jiang, Hong (Computers and Electronics in Agriculture, 2002)

Effects of harvesting regimes on carbon and nitrogen dynamics of boreal forests in central Canada: a process model simulation - Peng, Changhui; Jiang, Hong; Apps, Michael J.; Zhang, Yanli (Ecological Modelling, 2002)

TRIPLEX: a generic hybrid model for predicting forest growth and carbon and nitrogen dynamics - Peng, Changhui; Liu, Jinxun; Dang, Qinglai; Apps, Michael J; Jiang, Hong (Ecological Modelling, 2002)

Developing carbon-based ecological indicators to monitor sustainability of Ontario’s forests - Peng, Changhui; Liu, Jinxun; Dang, Qinglai; Zhou, Xiaolu; Apps, Mike (Ecological Indicators, 2002)